Implementasi Pembiayaan Akad Murabahah dalam Upaya Peningkatan UMKM di KSPPS Permata Barokah Jaya Kelurahan Pandaan - Siti Ayu Rochmaniah; Renny Oktafia (ITB AAS INDONESIA Surakarta, 2021)
Micro, Small and Medium Enterprises (MSMEs) are a group of people who work as business actors, who have a desire to increase personal income and also the wider community. However, this certainly requires special support from the Islamic Microfinance Institution itself, one of which is the Sharia Cooperative. This study aims to determine how the implementation of Murabahah Akad financing and efforts to increase Micro, Small and Medium Enterprises (MSMEs) at KSPPS Permata Barokah Jaya, Pandaan Village. Researchers chose to use qualitative research methods with a case study approach. The results of this study indicate that the implementation of the Murabahah Agreement which is in demand by many financing members at KSPPS Permata Barokah Jaya is in accordance with the principles of Sharia. However, efforts to increase Micro, Small and Medium Enterprises (UMKM) at KSPPS Permata Barokah Jaya are still not able to provide maximum financing for business actors, because the Murabahah Akad financing at KSPPS Permata Barokah Jaya is dominated by members who work as factory employees. This factory employee, is considered to be able to make it easier for the KSPPS Permata Barokah Jaya in surveying prospective members, as well as the inclusion of guarantees in the form of a member Salary ATM.